2017
DOI: 10.1016/j.compstruct.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Relative behaviour of premature failures in adhesively plated RC beam using controllable and existing parameters

Abstract: Retrofitting of RC beam by gluing a steel plate at the soffit has been a widely adopted technique due to its ease of use, calculations and having minimal variations on structural aesthetics; hence, a large number of such retrofitted structures exist today. However, such structures have also failed frequently due to the formation of premature failures such as peeling and debonding. The further investigations conducted in literature indicated that such undesirable failures can be effected by a large number of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Narayanamurthy et al (2012) have summarised key models to signify the importance of interfacial stresses that are responsible for debonding, over the stresses responsible to cause peeling rip-off failure. Others (Chen et al, 2006, Khan, 2018Khan et al, 2017b;Oehlers, 1992;Oehlers and Moran, 1990;Oehlers and Seracino, 2004) have identified the possible interaction between flexural cracks and interfacial cracks.…”
Section: Materials Models and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Narayanamurthy et al (2012) have summarised key models to signify the importance of interfacial stresses that are responsible for debonding, over the stresses responsible to cause peeling rip-off failure. Others (Chen et al, 2006, Khan, 2018Khan et al, 2017b;Oehlers, 1992;Oehlers and Moran, 1990;Oehlers and Seracino, 2004) have identified the possible interaction between flexural cracks and interfacial cracks.…”
Section: Materials Models and Methodsmentioning
confidence: 99%
“…As discussed before, peeling being a direct consequence of flexural crack at plate-end, therefore, it depends on the properties of concrete in tension as demonstrated by Khan et al (2017b). This required us to directly correlate the tension behaviour of CDP model with xFEM cohesive model.…”
Section: Peelingmentioning
confidence: 99%
See 3 more Smart Citations